2018
DOI: 10.1155/2018/5109615
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patients’ Adherence to Antiepileptic Medications at Dessie Referral Hospital, Chronic Follow-Up, South Wollo, Amhara Region, North East Ethiopia

Abstract: An epileptic seizure is a clinical event presumed to result from an abnormal and excessive neuronal discharge. The clinical symptoms are paroxysmal and may include impaired consciousness and motor, sensory, autonomic, or psychic events perceived by the subject or an observer. Epilepsy occurs when 2 or more epileptic seizures occur unprovoked by any immediately identifiable cause. And in the majority of patients with epilepsy, antiepileptic drugs effectively control their illness. However, more than 30% of peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 14 publications
8
21
1
Order By: Relevance
“…The finding of this review showed the magnitude of anti-epileptic medication non-adherence as it is in line with another similar study conducted on medication adherence of people with epilepsy (40%) [15]. However, the finding of the current review reported a higher magnitude of anti-epileptic medication non-adherence as compared to other reviews [48,57]. The possible explanation for the higher burden of anti-epileptic medication nonadherence in this review might be due to the more supernatural perception of epilepsy attributed by community members of Ethiopia than developed nations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The finding of this review showed the magnitude of anti-epileptic medication non-adherence as it is in line with another similar study conducted on medication adherence of people with epilepsy (40%) [15]. However, the finding of the current review reported a higher magnitude of anti-epileptic medication non-adherence as compared to other reviews [48,57]. The possible explanation for the higher burden of anti-epileptic medication nonadherence in this review might be due to the more supernatural perception of epilepsy attributed by community members of Ethiopia than developed nations.…”
Section: Discussionsupporting
confidence: 89%
“…There were fourteen primary studies included in our systematic review and meta-analysis. These studies were conducted across different regions of Ethiopia (two primary articles from Tigray [45,46], six at Amhara [47][48][49][50][51][52] two Oromia [53,54], two South Nation, Nationality and People (SNNPR) [22,55] and other two from Addis Ababa [40,56]. The sample size of primary studies included in this review was considerably variable ranging 88 to 450 participants.…”
Section: Original Characteristics Of Primary Studiesmentioning
confidence: 99%
“…Many people in Africa believe that epilepsy is contagious and can be spread by urine, saliva, atus, or feces excreted at all times or during a convulsion because of these unwilling to help or to touch the person who has fallen during a seizure lead to enormous social stigmas and lower QOL (3). A recent studies done in this hospital shows that 29.5% of epileptic patient had perceived their illness is not neurologic disorder rather they think it was a disease of spiritual concern (12).…”
Section: Introductionmentioning
confidence: 95%
“…Patient's quality of life assessment must be done in this hospital because of epileptic patients are usually taking AEDs for long period of time that may affect the patient's quality of life. In this hospital one-third of the epileptic patients had experienced side effects and more than 30% of people with epilepsy do not attain full seizure control even with the best available treatment regimen because of poor adherence to AEDs (12).…”
Section: Introductionmentioning
confidence: 96%
“…10,[13][14][15] Little is known, however, about the retention of hypertensive patients in rural populations, where the reasons are likely to be different. While financial difficulties, knowledge of the disease, poor social support, stigma and the occurrence of side effects have been identified as factors affecting adherence in epilepsy patients attending urban clinics, 16,17 data concerning rural epilepsy patients are sparse, although there are suggestions that the determinants of LTFU in rural areas may be different. For example, a study of epilepsy patients in rural clinics in Ethiopia found that the principal problems were travel difficulties and a preference for traditional remedies, 8,18 while in rural Zimbabwe, drug shortages and the distance from health facilities have been reported.…”
mentioning
confidence: 99%